An American treasure [compact disc] - Petty, Tom (Reprise, 2018)
Reprise Records release a career-spanning Tom Petty box set. The 60-track set unveils dozens of previously unreleased recordings, alternate versions of classic songs, rarities, historic live performances and deep tracks that spotlight Petty's remarkable depth and evolution as a revered and tremendously influential songwriter, recording artist and performer. This marks the first release of Tom Petty music since the artist's tragic passing in October 2017.